CXCR6 is a marker for protective antigen-specific cells in the lungs after intranasal immunization against Mycobacterium tuberculosis. - Lee, L; Ronan, E; de Lara, C; Franken, K; Ottenhoff, T; Tchilian, E; Beverley, P (2011)
Convincing correlates of protective immunity against tuberculosis have been elusive. In BALB/c mice, intranasal immunization with a replication-deficient recombinant adenovirus expressing Mycobacterium tuberculosis antigen 85A (adenovirus-85A) induces protective lower respiratory tract immunity against pulmonary challenge with Mycobacterium tuberculosis, while intradermal immunization with adenovirus-85A does not. Here we report that intranasal immunization with adenovirus-85A induces expression of the chemokine receptor CXCR6 on lung CD8 T lymphocytes, which is maintained for at least 3 months. CXCR6-positive antigen-specific T cell numbers are increased among bronchoalveolar lavage-recoverable cells. Similarly, intranasal immunization with recombinant antigen 85A with adjuvant induces CXCR6 expression on lung CD4 cells in BALB/c and C57BL/6 mice, while a synthetic ESAT6(1-20) peptide with adjuvant induces CXCR6 expression in C57BL/6 mice. Parenteral immunization fails to do so. Upregulation of CXCR6 is accompanied by a transient elevation of serum CXCL16 after intranasal immunization, and lung cells cultured ex vivo from mice immunized intranasally show increased production of CXCL16. Administration of CXCL16 and cognate antigen intranasally to mice previously immunized parenterally increases the number of antigen-specific T lymphocytes in the bronchoalveolar lavage-recoverable population, which mediates inhibition of the early growth of Mycobacterium tuberculosis after challenge. We conclude that expression of CXCR6 on lung T lymphocytes is a correlate of local protective immunity against Mycobacterium tuberculosis after intranasal immunization and that CXCR6 and CXCL16 play an important role in the localization of T cells within lung tissue and the bronchoalveolar lavage-recoverable compartment.